Examining the broader psychosocial effects of mass conflict on PTSD symptoms and functional impairment amongst West Papuan refugees resettled in Papua New Guinea (PNG). (May 2015) - Tay, Alvin Kuowei; Rees, Susan; Chan, Jack; Kareth, Moses; Silove, Derrick
Abstract: Mass conflict and displacement erode the core psychosocial foundations of society, but there is a dearth of quantitative data examining the long-term mental health effects of these macrocosmic changes, particularly in relation to posttraumatic stress disorder (PTSD) symptoms. In 2013, we conducted a cross-sectional community study (n = 230) of West Papuan refugees residing in Port Moresby, Papua New Guinea, testing a moderated-mediation structural equation model of PTSD symptoms in which we examined relationships involving the psychosocial effects of mass conflict and displacement based on the Adaptation and Development after Persecution and Trauma (ADAPT) model, a trauma count (TC) of traumatic events (TEs) related to mass conflict, and a count index of current adversity (AC). A direct and an indirect path via AC led to PTSD symptoms. The ADAPT index exerted two effects on PTSD symptoms, an indirect effect via AC, and a moderating effect on TC. PTSD symptoms were directly associated with functional impairment. Although based on cross-sectional data, our findings provide support for a core prediction of the ADAPT model, that is, that undermining of the core psychosocial foundations of society brought about by mass conflict and displacement exerts an indirect and moderating influence on PTSD symptoms. The path model supports the importance of repairing the psychosocial pillars of society as a foundation for addressing trauma-related symptoms and promoting the functioning of refugees. Highlights: Psychosocial disruptions caused by mass conflict influence posttraumatic symptoms. We tested the ADAPT model amongst a sample of West Papuan refugees. The ADAPT index moderated the effects of traumatic events in the path to PTSD symptoms. The ADAPT index was mediated by ongoing adversity in a second path to PTSD symptoms. Our findings support a multi-tiered approach to designing recovery programs for refugees.